International Conference on Transportation and Development 2021. selected papers from the International Conference on Transportation and Development 2021, June 8-10, 2021 - Bhat, Chandra R. 1964- (American Society of Civil Engineers, 2021)
This collection includes 39 peer-reviewed papers from the conference. Topics include: sustainable community transportation systems; road construction investment and financing; paving materials; and transportation availability and land use and development. This collection will be of interest to transportation engineers and researchers, policymakers, planners, and operations managers in communities of all sizes and locations.